2023
DOI: 10.3390/molecules28052203
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Donor–Acceptor Linear Conjugated Polymers Involving Cyanostyrylthiophene Linkages for Visible-Light-Driven Hydrogen Production

Abstract: In this paper, an atom- and step-economic direct C-H arylation polymerization (DArP) strategy was developed to access cyanostyrylthiophene (CST)-based donor–acceptor (D–A) conjugated polymers (CPs) used for photocatalytic hydrogen production (PHP) from water reduction. The new CST-based CPs CP1–CP5 with varied building blocks were systematically studied by X-ray single-crystal analysis, FTIR, scanning electron microscopy, UV-vis, photoluminescence, transient photocurrent response, cyclic voltammetry measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In addition, the presence of vinyl bonds in the main aromatic polymeric chain can increase the degree of coplanarity of the main polymer chain, as vinyl bonds can reduce spatial hindrance on continuous aromatic rings. Our studies have revealed that 2-styrylthiophene-based linear conjugated polymers (CPs) with a -CN substituent have impressive PHP performance [31,32]. The dibromocyanostilbene containing electron-withdrawing cyano groups in the ethylene position, as diarylethene derivatives with D-A architecture, is expected to serve as an excellent skeleton for D-A CP-based efficient photocatalysts in PHP reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the presence of vinyl bonds in the main aromatic polymeric chain can increase the degree of coplanarity of the main polymer chain, as vinyl bonds can reduce spatial hindrance on continuous aromatic rings. Our studies have revealed that 2-styrylthiophene-based linear conjugated polymers (CPs) with a -CN substituent have impressive PHP performance [31,32]. The dibromocyanostilbene containing electron-withdrawing cyano groups in the ethylene position, as diarylethene derivatives with D-A architecture, is expected to serve as an excellent skeleton for D-A CP-based efficient photocatalysts in PHP reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the PL and TPR results, the EIS experiments demonstrate that the order of the Nyquist circle radius is TSO 2 @TiO 2 < TS@TiO 2 < TFl@TiO 2 . Therefore, the smallest arc radius of the Nyquist plot for TSO 2 @TiO 2 means it has lower interfacial resistance and excellent charge mobility characters [ 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…This enhanced planarity potentially facilitates faster electron and hole transfer, thereby enhancing charge transfer efficiency. [56][57][58][59] To assess the extent of particle aggregation in the hydrogen evolution solution, we employed uorescence microscopy (FM) to analyse particle sizes. FM offers the advantage of exciting polymers with various wavelengths of light sources and capturing images of aggregates in their native state.…”
Section: Discussion Of Hydrogen Evolutionmentioning
confidence: 99%